The first debt ceiling crisis - Kenneth D. Garbade (Federal Reserve Bank of New York, 2016)
In the second half of 1953 the United States, for the first time, risked exceeding the statutory limit on Treasury debt. This paper describes how Congress, the White House, and Treasury officials dealt with the looming crisis - by deferring and reducing expenditures, monetizing "free" gold that remained from the devaluation of the dollar in 1934, and, ultimately, raising the debt ceiling.
Keywords: E42; H63; N22; 330; debt ceiling; monetization of gold; U.S. Treasury